Pengembangan perangkat pembelajaran matematika SMP kelas VIII semester genap dengan model problem-based learning - Maria Trisna Sero Wondo (PYTHAGORAS Jurnal Pendidikan Matematika, 2017)
Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran matematika SMP kelas VIII semester genap dengan model problem-based learning berorientasi pada prestasi belajar, kemampuan pemecahan masalah, dan sikap percaya diri siswa. Jenis penelitian ini adalah penelitian pengembangan model Plomp (penelitian awal, pengembangan, penilaian). Subjek penelitian ini adalah guru dan siswa kelas VIII SMP Swasta Katolik Maria Goretti Ende. Analisis data dilakukan dengan mengkonversi data kuantitatif berupa skor hasil penilaian menjadi data kualitatif berupa nilai standar skala lima. Penelitian ini menghasilkan perangkat pembelajaran matematika kelas VIII semester genap berupa RPP dan LKS. Dari hasil validasi ahli, skor penilaian guru, penilaian siswa, observasi keterlaksanaan kegiatan pembelajaran, tes prestasi belajar, tes kemampuan pemecahan masalah, dan angket sikap percaya diri menunjukkan bahwa RPP dan LKS adalah valid, praktis, dan efektif.Kata Kunci: Perangkat pembelajaran, problem-based learning, prestasi belajar, pemecahan masalah, percaya diri Developing Mathematics Learning Kits Using the Problem-Based Learning Model for Grade VIII of JHS in the Even Semester AbstractThis study aimed to produce mathematics learning kits using the problem based learning model oriented to the learning achievement, problem solving skill, and self-confidence for Grade VIII students of the junior high school (JHS) in the even semester. This study was and development study used the development model by Plomp (preliminary study, development, evaluation). The research subjects were teachers and students of Grade VIII of Swasta Katolik Maria Goretti Ende. The analysis of the data was done by converting the quantitative data in the form scores as the results of the evaluation into qualitative data in the form of five-scale standard scores. This study produce mathematics learning kits in the form of lesson plans and student worksheets for Grade VIII students of the junior high school in the even semester. Of the results of expert validation, a teacher evaluation scores, a students evaluation scores, an observation for the implementation of learning activities, a learning achievement test, a problem solving skil test, and a self-confidence questionnaire show that lesson plans (RPP)  and student worksheets (LKS) is valid, practical, and effective. Keywords: learning kits, problem-based learning, learning achievement, problem solving, self-confidence